Fairy tale traditions in amateur and professional young writers’ creativity - Zolotova, Tatiana A.; Efimova, Natalia I.; Plotnikova, Ekaterina A.; Troshkova, Anna O. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The turn of the 21st century has seen Russian writers’ increased interest in the genre of fairy tale. This paper discusses young Russian writers’ approaches to fairy tale traditions in texts of their own. The subjects of the study consisted of the Debut Prize winners and the so-called amateur writers (fans of Tolkien’s and Rowling’s books, and gamers) and their literary works. The study is aimed at establishing main trends in usage of folklore traditions in the first two decades of the 21st century; the paper is also concerned with examining similarities and differences between two generations of modern Russian writers in the matter of their approaches to classical heritage. To compare fairy tale texts, Vladimir Propp’s narrative model has been applied. One of the central claims of the study is that young authors tend to emulate literary samples by prominent contemporary Russian writers (mostly by Lyudmila Petrushevskaya). Thus, an efficient way of creating a contemporary fairy tale by a young author is to immerse its characters into the modern reality that is presented in a variety of its manifestations – from everyday routine to philosophic ideas. The young writers’ texts display such traditional features of literary folklorism as genuine fairy tale plots and motifs, their structural and style models, characters, magical objects, and the artistic device of estrangement.